Urinary Cystatin C, Glucose, Urea, and Electrolytes in Dogs at Various Stages of Chronic Kidney Disease - Anna K. Selin; Inger Lilliehöök; Emma M. Strage; Anders Larsson; Lena Pelander (Journal of Veterinary Internal Medicine)
ABSTRACT Background There is limited knowledge of urine analytes in different stages of chronic kidney disease (CKD) in dogs. Objectives To study markers in urine and fractional excretion (FE) of markers in dogs of different stages of CKD and a healthy control group (C). Animals Fifty dogs in various stages of CKD and a control group of 30 healthy dogs. Methods In this cross‐sectional observational study, dogs presenting to a referral hospital and given a diagnosis of CKD using standard methods, and healthy dogs, were included. Urinary cystatin C (uCysC), glucose (uGlu), protein (uProt), creatinine (uCr), urea (uUrea), sodium (uNa), potassium (uK), chloride (uCl), calcium (uCa), and phosphate (uP) were measured with an automated chemistry analyzer. Included analytes were normalized to uCr, FE of electrolytes and urea was calculated, and results compared among groups. Results Age, bodyweight, and sex were not different among groups. Urinary CysC/uCr and FE of electrolytes increased with IRIS stage. Median (IQR) for uCysC/uCr was 0.08 (0.04–0.25) 10−3 in dogs with CKD stage 1 and 0.03 (0.02–0.045) 10−3 in control dogs (p = 0.0002). Conclusion and Clinical Importance Urinary CysC might be a potential marker of early CKD, preferably as part of a panel of urinary markers. FE of electrolytes seemed to depend on the serum creatinine level in dogs with azotemic CKD.